THE CURRENT STATE OF PREPARING FUTURE OLIGOPHRENOPEDAGOGUES FOR PROFESSIONAL ACTIVITY IN THE PROCESS OF INDEPENDENT LEARNING (Western European Journal of Modern Experiments and Scientific Methods, 2024)
This article examines the current state of preparing future oligophrenopedagogues for professional activity in the process of independent learning. The study analyzes the role of independent learning in developing professional competencies, methodological readiness, and practical skills necessary for working with children with intellectual disabilities. Particular attention is paid to the effectiveness of independent learning tasks in enhancing students’ ability to apply theoretical knowledge in real educational and correctional settings. The article also identifies existing challenges in organizing independent learning, including insufficient methodological support and limited integration with practical training. The findings emphasize the need to improve the structure and content of independent learning to ensure high-quality professional preparation of future oligophrenopedagogues.